REVIEW OF UZBEK LITERATURE: FROM THE BEGINNING OF THE APPEARANCE TO THE PRESENT DAY (Scientific journal of the Fergana State University, 2023)
The article discusses the features of Uzbek literature from the beginning of its appearance to the present day. National literature differs from the literature of other peoples, firstly, in its traditions, national features of the characters, and the originality of the depicted life. In this regard, the works of Uzbek writers of each individual period depict the Uzbek spirit, the Uzbek way of life, the Uzbek character, and important themes and ideas of the Uzbek people. Motives of dissatisfaction with the social system, patriotism and civic pathos begin to appear in the work of poets from different periods.